Stenting of Iliac Artery through Brachial Approach - Hossain, GMM; Mamun, MAA; Dey, NK; Mondol, NC; Jamaluddin, M (Cardiovascular Journal, 2014)
In some cases the iliac artery occlusive disease cannot be approached through standard access. The preferred access sites are the ipsilateral retrograde femoral and the contralateral antegrade cross-over, although occasionally these approaches do not allow an effective engagement of the lesion, especially when there is a total occlusion or complex aortoiliac lesion. We are reporting a case of iliac artery stenting through brachial approach.This technique is safe and effective. It provides enough support for stiff balloon or stent catheter to be advanced through this long sheath. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18360 Cardiovasc. j. 2014; 6(2): 164-166